The Location of Women's Prisons and the Deterrence Effect of 'Harder' Time - Kelly Bedard; Eric Helland (Claremont McKenna College, Department of Economics, 2000)
Most studies of the deterrence effect of incarceration treat a year in prison as having the same deterrence effect regardless of the conditions of incarceration. In contrast, we estimate both the impact of custody rate and prison location changes on female crime rates. We take advantage of the natural experiment created by recent expansions of the female penal system; many states witnessed a rapid doubling of prison capacity. The physical expansion of the penal system decreased the distance to prisons for some cities while increasing it for others. Movement in both directions is particularly helpful because it ensures that we are not identifying relationships off coincidental one-directional trends. Our results suggest that prison location has a sizable deterrence effect. Increasing the average distance to a woman's prison by 40 miles reduces the female violent crime rate by approximately 7 percent.
Keywords: 330